Internalization and recycling of 5-HT(2A) receptors activated by serotonin and protein kinase C-mediated mechanisms - Bhattacharyya, Samarjit (National Academy of Sciences, 2002)
Serotonin (5-HT), a major neurotransmitter, has a large number of G protein-coupled receptors in mammals. On activation by exposure to their ligand, 5-HT(2) receptor subtypes increase IP(3) levels and undergo desensitization and internalization. To visualize the receptor in cells during these processes, we have constructed a 5-HT(2A)-enhanced GFP (SR2-GFP) fusion receptor. We show that this fusion receptor undergoes internalization on exposure to its natural ligand, 5-HT. Because 5-HT(2A) receptors activate the phospholipase C pathway, we studied the effect of protein kinase C (PKC) on the internalization process and found that activation of PKC by its specific activator phorbol 12-myristate 13-acetate, in the absence of 5-HT, leads to internalization of the receptor. Moreover, inhibition of PKC by its inhibitor sphingosine in the presence of 5-HT prevents the internalization process, suggesting that activation of PKC is sufficient and necessary for the internalization of 5-HT(2A) receptors. We also show that SR2-GFP recycles back to the plasma membrane after 5-HT-dependent internalization, suggesting a mechanism for resensitization. In addition, receptors that have been internalized on addition of phorbol 12-myristate 13-acetate in the absence of 5-HT also recycle to the surface, with a time course similar to that seen after activation of the receptors by 5-HT. Our study suggests that 5-HT(2A) receptors internalize and return to the surface after both serotonin- and PKC-mediated processes. This study reveals a role for PKC in receptor internalization and also shows that 5-HT(2A) receptors are recycled.